Food Online Business Challenges During the Pandemic in Medan City - Yudi Bimantaka; Sugeng Arifandi Banurea; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
This research aims to find out the challenges of food business by using e-business in the city of Medan and some UINSU students who sell food or small snacks. This study uses qualitatively derifrift by collecting observational data, documentation, and interviews. The results showed: 1) can still sell online at this time (covid 19). 2) The common challenge felt or experienced is, consumers who want to be fast and instant, feel afraid of failing in trying new things such as selling online in times of pandemic like this, must be extra in attracting customers who are not as usual. 3) There is a way to deal with these challenges by promoting merchandise through social media even though it has to increase the cost to do the promotion